Mathematical Patterns in Surah Al-'Alaq 1-5 - Reza Oktiana Akbar; Gina Amalia; Indah Nursuprianah (Yayasan Adra Karima Hubbi, 2024)
TheQur'an is a reference for all numbers such as odd and even. Even odd numbers are numbers that Allah SWT likes and even numbers are the complement of odd numbers. The Qur'an contains many miracles including the miracle of the number 19 and many letters that describe the pattern of multiples of 19 in terms of words, letters and verses, one of the letters related to the number 19 is Surah Al-'Alaq. This study aims to find mathematical patterns and the meaning of numbers contained in Surah Al-'Alaq verses 1-5. Surah Al-'Alaq verses 1-5 were chosen because they have content and privileges. Al-'Alaq is the first revelation of the Nabi Muhammad SAW, this letter has hidden messages and values of education, divinity, and reasoning. So that humans can continue to learn and understand what they do not know. This type of research is descriptive qualitative which reveals the mathematical patterns contained in Surah Al-'Alaq verses 1-5 described or presented using numbers with the literature study method. The data used are the arrangement numbers in Surah Al-'Alaq 1-5. The results of the study found that there are 5 patterns in Surah Al-'Alaq verses 1-5 and there are multiples of 3. Mathematical patterns are important for understanding, they can help students solve problems and identify relationships in various contexts.